PENGARUH PEMAHAMAN AKUNTANSI PELAKU USAHA, KUALITAS INFORMASI LAPORAN KEUANGAN, DAN KOMPETENSI SDM TERHADAP KINERJA UMKM DI YOGYAKARTA - Eta Indriasari; Kusuma, Manggar (Jurnal Ekonomi Dan Bisnis, 2022)
The purpose of this research is to determine whether there is a positive influence between the understanding of business actors accounting, the quality of financial statement information, and the competence of human resources on the performance of MSMEs. The object of this research is the MSMEs in the Special Region of Yogyakarta. The sample selection method used in this research is purposive sampling with the criteria for MSME actors in the Special Region of Yogyakarta who made financial records. Data collection techniques are questionnaires, there are google forms and hardcopy questionnaries. There were 126 respondents who became the sample in this research. The research model used in this study is multiple regression analysis. The results of this research indicate that: (1) understanding of business actors accounting has a positive effect on the performance of MSMEs; (2) the quality of financial statement information does not affect the performance of MSMEs; (3) the competence of human resources has a positive effect on the performance of MSMEs.